2014
DOI: 10.1161/atvbaha.113.302667
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD40 + and CD86 + B Cell Subsets Demonstrate Opposing Associations With Risk of Stroke

Abstract: + CD86+ B cells were associated with higher risk for development of a stroke event and increased release of proinflammatory cytokines from mononuclear leukocytes. Conclusions-These

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 57 publications
(75 reference statements)
3
27
0
1
Order By: Relevance
“…Similar to our observations regarding the memory B cells, it has previously been shown that patients with high CD40 + B‐cell percentages exhibit a lower stroke risk 22. Accordingly, we also observed a lower rate of cerebrovascular events in patients with high memory cell numbers (0.6%) compared with patients with low numbers (3.6%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our observations regarding the memory B cells, it has previously been shown that patients with high CD40 + B‐cell percentages exhibit a lower stroke risk 22. Accordingly, we also observed a lower rate of cerebrovascular events in patients with high memory cell numbers (0.6%) compared with patients with low numbers (3.6%).…”
Section: Discussionsupporting
confidence: 91%
“…Categorical variables were indicated as percentages and compared by chi‐square or Fisher's exact tests where appropriate. As confounders, we selected variables that associate with CVD risk, but also influence B‐cell numbers and have been established as confounders in literature, including age, sex, smoking, history of coronary artery disease, and glomerular filtration rate 22, 44, 45, 46, 47. We also tested for a sex interaction between the association of B cells and cardiovascular end points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Blocking CD28 post stroke reduces infarct size, improves behavioral outcomes, and reduces the inflammatory response. 20,21 Our study suggests that a decrease in let7i may promote this detrimental immune response post stroke by increasing expression of CD86.…”
Section: Neurology 87 November 22 2016mentioning
confidence: 99%
“…The authors also identified CD4 + IL-21 + T cells in human post-mortem ischemic brain tissues. Mantani et al in their recent clinical stroke study focused on B lymphocytes and identified the role of two B-cell subsets CD19 + CD40 + (decreasing) and CD19 + CD86 + (increasing) altering the risk for development of a stroke event [43].…”
Section: Adaptive Immune Responses and Role Of Bridge Cellsmentioning
confidence: 99%